ASSESSING THE EFFECTIVENESS OF AN ECO-ENZYME TRAINING OF TRAINERS (TOT) PROGRAM IN ENHANCING ENVIRONMENTAL LITERACY AND SOCIAL ENTREPRENEURSHIP THROUGH AN SROI APPROACH - Aswin D. Hadisumarto; Imbuh Sulistyarini; Ikrar Genidal Riadil (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
ABSTRACT The accumulation of organic waste in urban areas has become a significant environmental challenge that requires sustainable solutions through educational and participatory approaches. This study aims to evaluate the social, environmental, and economic impacts of a Community Service Program (PkM) in the form of a Training of Trainers (ToT) on Eco-Enzyme production implemented at SDN Beji Timur 1, Depok City. The program involved 20 teachers and 42 students as primary participants, who subsequently disseminated their knowledge to 142 students and 30 additional teachers. This study employed a quantitative evaluative approach using the Social Return on Investment (SROI) framework to assess the social value generated relative to the program investment of IDR 40,000,000. The research process included stakeholder identification, outcome mapping, determination of benefit indicators, calculation of social value, and SROI ratio analysis. The findings revealed an SROI ratio of 3.95:1, indicating that every IDR 1 invested generated IDR 3.95 in social, environmental, and economic benefits. The major outcomes included improved teacher and student capacity in organic waste management, enhanced environmental literacy, strengthened pro-environmental behavior, and potential cost savings through the use of Eco-Enzyme as an alternative to chemical-based products. These findings demonstrate that the Eco-Enzyme ToT program generates substantial social value and has strong potential to be developed as an environmental learning model as well as a school-based living laboratory for fostering social entrepreneurship among elementary school communities. ABSTRAK Penumpukan sampah organik di wilayah perkotaan menjadi permasalahan lingkungan yang memerlukan solusi berkelanjutan melalui pendekatan edukatif dan partisipatif. Penelitian ini bertujuan untuk mengevaluasi dampak sosial, lingkungan, dan ekonomi dari Program Pengabdian kepada Masyarakat (PkM) berupa Training of Trainers (ToT) pembuatan Eco-Enzyme di SDN Beji Timur 1 Kota Depok. Program melibatkan 20 guru dan 42 siswa sebagai peserta utama yang selanjutnya mendiseminasikan pengetahuan kepada 142 siswa dan 30 guru lainnya. Penelitian menggunakan pendekatan kuantitatif evaluatif dengan metode Social Return on Investment (SROI) untuk mengukur nilai manfaat sosial yang dihasilkan dibandingkan dengan investasi program sebesar Rp40.000.000. Tahapan penelitian meliputi identifikasi pemangku kepentingan, pemetaan perubahan yang terjadi, penentuan indikator manfaat, penghitungan nilai manfaat sosial, serta analisis rasio SROI. Hasil penelitian menunjukkan bahwa program menghasilkan rasio SROI sebesar 3,95:1, yang berarti setiap Rp1 yang diinvestasikan mampu menghasilkan manfaat sosial, lingkungan, dan ekonomi senilai Rp3,95. Manfaat utama yang teridentifikasi meliputi peningkatan kapasitas guru dan siswa dalam pengelolaan sampah organik, peningkatan literasi lingkungan, penguatan perilaku ramah lingkungan, serta potensi penghematan biaya melalui pemanfaatan Eco-Enzyme sebagai alternatif produk berbahan kimia. Temuan ini menunjukkan bahwa program ToT Eco-Enzyme memiliki nilai sosial yang tinggi dan layak dikembangkan sebagai model pembelajaran berbasis lingkungan sekaligus laboratorium sosial (living lab) untuk menumbuhkan jiwa kewirausahaan sosial di sekolah dasar.